Nas entre-falhas da linha-vida : experiências de gênero, opressões e liberdade em uma prisão feminina - Daniela Tiffany Prado de Carvalho (2014)
Women represent roughly 10% of Minas Gerais’ incarcerated population. However, this number has grown significantly over the past years. These women are generally young, non white, poorly educated and with low socioeconomic status. In this sense, there’s a process of naturalization of the average female criminal, which demonstrates how selective the penal system can be. At the same time that women’s participation in crimes is considered atypical, the prison space is seen as the right place for certain types of women. Furthermore, for these women, the prison system will prescribe a treatment that consists in bringing them back to what a typical woman “ought be”: mother, wife, caregiver. Through interviews with 12 women serving sentences at the Complexo Penitenciário Feminino Estevão Pinto, in the state of Minas Gerais, we advance in understanding how they interpret their own incarceration, their perspectives on the actions that led to their imprisonment, their exposure to violent environments, and other meaningful aspects of their lives, both within and outside the prison system. We analyze the socio-demographic characteristics of these women not in order to reiterate the aforementioned process of naturalization but to reflect on the selectivity of our penal system. By presenting “who they are” and questioning “why are they incarcerated?”, we investigate some of the factors that have contributed to the rapid rise in the female prison population. Thus, we examine whether the growth in female imprisonment can be attributed to social exclusion, criminalization of poverty, and/or changes in prosecution and sentencing patterns.